Constitutional Justice Administration under Section 213 of the Constitution of the Kingdom of Thailand B.E. 2560 (2017) : A Case Study of the Role of the Ombudsman in the Constitutional Complaint Mechanism - auiyaput, adithep (Journal of Thai Ombudsman, 2026)
This article examines the administration of constitutional complaint cases under Section 213 of the Constitution of the Kingdom of Thailand B.E. 2560 (2017), with particular emphasis on the role of the Ombudsman as an intermediary institution responsible for filtering petitions before they reach the Constitutional Court. The study adopts the framework of constitutional justice administration to analyze the structural relationship between individuals’ right of access to constitutional justice and the necessity of effective case management within the Constitutional Court. The research employs a doctrinal and comparative approach, drawing on the experiences of Germany, Austria, the Republic of Korea, and Türkiye to evaluate international standards concerning admissibility criteria and filtering mechanisms. The findings indicate that while filtering mechanisms are an indispensable component of modern constitutional complaint systems, their legitimacy and effectiveness depend on three key conditions: (1) clarity and predictability of admissibility criteria, (2) transparency and reason-giving in the filtering process, and (3) the exercise of filtering functions under judicial control. These conditions are essential to prevent filtering mechanisms from becoming institutional barriers that undermine the fundamental right of access to constitutional justice. In the Thai context, the study reveals that the current system under Section 213 suffers from both legal and structural limitations, particularly the absence of clear admissibility standards and the lack of systematic reasoning at the Ombudsman stage. These deficiencies risk constraining individuals’ effective access to the Constitutional Court. The article proposes a three-tier reform framework—covering interpretive practice, subordinate legislation, and institutional structure—to realign the system with the principles of constitutional justice administration and international standards. Such reforms are expected to enhance both the efficiency of case management and the legitimacy of constitutional rights protection in the long term.